2021
DOI: 10.1002/capr.12470
|View full text |Cite
|
Sign up to set email alerts
|

Using rich data to inform student mental health practice and policy

Abstract: The collection and use of rich data on student mental health are necessary to inform practice and policy, and ultimately lead to improved outcomes. Here, rich data refers to the combination of large and representative data sets, as well as detailed accounts of lived experiences and perspectives. We argue that such data are necessary to respond to the diverse and ever‐changing needs of students while building an evidence base for current and emerging services and staff roles. We provide suggestions for moving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…From a discursive perspective, we are thus interested in what saying ‘I’m triggered’ does when expressed publicly in the university or framed privately for the self. This perspective aligns with Broglia et al's (2021) suggestion that assessing students’ mental health must be done with attention to their lived experiences, using rich and complex data, as well as traditional quantitative forms.…”
Section: Discourse Theorysupporting
confidence: 72%
See 1 more Smart Citation
“…From a discursive perspective, we are thus interested in what saying ‘I’m triggered’ does when expressed publicly in the university or framed privately for the self. This perspective aligns with Broglia et al's (2021) suggestion that assessing students’ mental health must be done with attention to their lived experiences, using rich and complex data, as well as traditional quantitative forms.…”
Section: Discourse Theorysupporting
confidence: 72%
“…This may also be part of a pendulum swing away from the ‘strengths‐based’ movement in psychology that critics argue may leave behind those most vulnerable and overemphasise individual, privatised ways of building resistance without addressing the social structures that oppress and keep individuals vulnerable (Becker & Marecek, 2008; Gray, 2011; McDonald & O’Callaghan, 2008). Further, this change in focus may be supported by Broglia et al's (2021) call for complex and meaningful data in assessing students’ mental health and our ability to serve mental health populations.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Connell et al (2008) found that 31.5% of clients in a sample of students attending university counselling across seven institutions did not have linked outcome data, a percentage that is likely to be an underestimation due to other data also being excluded. Notwithstanding the increasing policy levers, in the absence of any mandated call to use sessional measures in university counselling and mental health services, it will remain a challenge for services to progress this agenda (Broglia et al, 2021). However, there is an increasing body of literature that may provide supporting arguments to enable service leaders and individual practitioners to give the adoption of sessional measures greater consideration.…”
Section: Introductionmentioning
confidence: 99%